Peran Pendamping Program Keluarga Harapan (PKH) dalam Mengatasi Kemiskinan Keluarga Penerima Manfaat (KPM) di Kecamatan Taman Kabupaten Pemalang - Phina Karina; Amin Yusuf (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Family Hope Program (PKH) is a social assistance program of the Ministry of Social Affairs which aims to improve the welfare of the poor through cash assistance and social assistance. This program is used to improve access to education, health, and social welfare, therefore assistance is provided for school children, toddlers, pregnant women, the elderly, and people with disabilities. This study uses a descriptive qualitative method with a natural approach. The study was conducted in Taman District, Pemalang Regency with research subjects including PKH Coordinators, PKH Companions, and PKH KPM members. Data collection in this study was conducted by interviews, observations and documentation. The results of the study show that PKH companions play an important role as facilitators, educators, representatives and technicians in supporting Beneficiary Families (KPM). The facilitative role includes motivation and support for KPM in fulfilling their obligations. As a companion educator, he is able to socialize PKH policies well and provide skills training to KPM. In the role of the companion representative, he always voices the needs of the KPM to the relevant parties, while in the technical role, the companion is able to handle the administration of assistance, data updates and monthly reporting of the companion well. The supporting factors in the success of the assistance are from the government and stakeholders. However, the obstacles faced by the facilitators are the low participation of KPM in carrying out P2K2 activities and the dishonesty of some KPM who should not be eligible to receive assistance.